1989
DOI: 10.1007/bf00120154
|View full text |Cite
|
Sign up to set email alerts
|

Report of a 60 month study on litter production, changes in soil chemical properties and productivity under Poplar (P. deltoides) and Eucalyptus (E. hybrid) interplanted with aromatic grasses

Abstract: Quantity of litter fall, its chemical composition, nutrient addition and changes in chemical constituents of soil were studied under agroforestry systems involving Populus deltoides and Eucalyptus hybrid tree with intercrops of Cymbopogon martinii Wats and Cymbopogonflexuosus Wats in the tarai tract of Kumaon hills of U.P. India. P. deltoides had significantly more diameter (63%) as compared to E. hybrid. There was decrease in herb (5.4%) and oil yield (15.4%) of grasses due to trees, but both the grasses did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 4 publications
2
14
0
1
Order By: Relevance
“…The nutrient returned to the soil through senescent leaves was in the order of N>K>P. Pattern of nutrient concentration in senescent leaves varied according to the species. Similar to our results, Singh et al (1989) and Lodhiyal & Lodhiyal (1997) reported the returned nutrient content by leaf litter in the order of N>K>P in Populus deltoides plantations in moist plain area in the north of India. However, Mahmood et al (2009Mahmood et al ( , 2011 reported nutrient release from leaf litter of three tree species in Bangladesh follows the order of K>N>P.…”
Section: Discussionsupporting
confidence: 91%
“…The nutrient returned to the soil through senescent leaves was in the order of N>K>P. Pattern of nutrient concentration in senescent leaves varied according to the species. Similar to our results, Singh et al (1989) and Lodhiyal & Lodhiyal (1997) reported the returned nutrient content by leaf litter in the order of N>K>P in Populus deltoides plantations in moist plain area in the north of India. However, Mahmood et al (2009Mahmood et al ( , 2011 reported nutrient release from leaf litter of three tree species in Bangladesh follows the order of K>N>P.…”
Section: Discussionsupporting
confidence: 91%
“…The results were very astonishing and it was observed that about 33.3% -83.3% carbon can be enhanced in soil by introducing tree species. It was also concluded that SOC was more where Populus deltoides was grown as compared to Eucalyptus (Singh et al, 1989).…”
Section: Soil Carbonmentioning
confidence: 99%
“…Wider use of poplar can contribute to European Union goals to ensure 20% of its energy consumption from renewable resources until 2020 and continue further in the future (Jansons et al, 2014). Poplar based agroforestry has the capability of enhancing soil organic carbon up to 83% (Singh et al, 1989).…”
Section: Introductionmentioning
confidence: 99%